THz time‐domain spectroscopy and IR spectroscopy on MoS2. Issue 12 (3rd November 2016) - Arcos, David; Gabriel, Daniel; Dumcenco, Dumitru; Kis, Andras; Ferrer‐Anglada, Núria
Abstract : In the increasing research field of 2D materials such as graphene, molybdenum disulfide MoS2 has attracted great interest due to the existence of a direct bandgap in monolayer MoS2, which gives the possibility of achieving MoS2 field‐effect transistors or optoelectronic devices. We analyzed by THz time‐domain spectroscopy (THz‐TDS) up to 2 THz and infrared (IR) spectroscopy, CVD‐obtained MoS2 using either S or H2 S gas as a sulfur precursor, grown on a sapphire substrate. From THz‐TDS we obtained the transmittance, conductivity, and attenuation. From IR spectroscopy on the same samples, we deduced the transmittance in the IR frequency range. We observed the coherence of both spectroscopic methods. The advantage of the THz‐TDS method is that we can get significant parameters related to the sample quality without the need for depositing any electrical contact or sample preparation. Our results show that at high frequencies MoS2 is even better than graphene as a material for optoelectronic devices.